â€œTaking it for grantedâ€: The utilization of pragmatic aspects in entertainment news reporting on Instagram - Khalisah, Alya; Anjarningsih, Harwintha Yuhria (Universitas Pendidikan Indonesia, 2020)
Instagram has been one of the main platforms for real-time information seeking for the last five years (Schroeder, 2018). The kind of information that people look for includes entertainment news. The present study aims to examine the way an entertainment news account presents its news content using different pragmatic techniques and how these techniques affect its brand image because minor attention has been paid to purpose-oriented accounts. To fulfill the aim, there are two research problems that are addressed: (1) what are the most common pragmatic techniques used in the captions? And (2) what significance does each technique have in presenting the news and shaping the brand image? Therefore, 36 sample captions from E! News Instagram account, as the most followed entertainment news account on Instagram, were taken, observed, and analyzed using a framework developed by Al-Hindawi and Mehdi (2017) in their article about a pragmatic analysis on American and British website-based entertainment news that focuses on three pragmatic pillars, namely presupposition, Grice’s conversational maxims, and allusion. The study found that in the case of E! News, presupposition, violation to Grice’s conversational maxims, and allusion are not merely used to keep the content interesting, but they respectively hold important roles in shaping the content of the news, engaging audience’s interest, and creating a good brand image.